The representation of masculinity in a Malaysian televised show / Uma Rani A Rethina Velu - Uma Rani , A Rethina Velu (2020)
This study examines the representation of masculinity in a Malaysian televised show, Oh My English! using a multimodal Critical Discourse Analysis from four perspectives. Firstly, this study analyses the verbal processes significant in the reflection of the Other among five main male social actors and with other character roles. Secondly, the non-verbal processes are simultaneously analysed via visual interpretation. Thirdly, these two processes overlap with the analysis of social actions in the performance of masculinity. Finally, how ideological assumptions reflect on masculinity are analysed via the two processes and social actions among the five main social actors along with the other character roles. The overall analysis involves different frameworks in order to inter-discursively examine the reflection of the Other, crucial from a critical perspective that relies on concepts and studies of both global and local domains. A single component framework of three of van Leeuwen’s networks (2008) contributes firstly as a tool for analysis entering into a critical and socio-semantic approach. Whereas, Kress and van Leeuwen’s (1996, 2006) multi-semiotic approach contributes in examining various hierarchical classification of masculinities via the two processes embedded with social actions. Connell’s (1995, 2005) concept of hegemonic masculinity in relation to language and gender and relevant notions such as representation, ideology and hegemony play an important role. These concepts contribute to the realisation of action and reaction processes through depiction of masculinity in accordance to events within context of Oh My English! The realisation of rhetorical and stereotypical strategies via individual and collective performances together with dynamics of various forms of authorisation as well as non-human instruments play a significant role either directly or indirectly in the reflection of the negative Other. Dominance of one group of men over another male peer within the same group along with power relations contribute to different discourses from a hegemonic viewpoint among the social actors. Apart from the highest positioning in hierarchy of masculinity that is hegemonic, complicit and subordinate forms established via backgrounding leading to marginalisation. Crucially, hegemonic discourses co-present with effeminacy in relation to heterosexual cultural norms, beliefs and values contribute to problematic discourses on masculinity. Common sense via agency invested through traditional, personal and role model authorisation via institutional setting further allows assimilation and inclusion of one group of young men in comparison to another with negative evaluation. Prevalence of various authorisations contributes to another dimension of problematic contradictions leading to legitimisation and de-legitimisation of discourses. Within the scene events, the two processes give way to three main schemas as composites towards an inter-discursive analysis of re-contextualised discourses. The three composites are in the reflection of the Other via social actions of male fantasy and gaze, machismo with competition, and male preserve football. These three composites as topics contribute further to the analysis and findings towards the reflection of ideological assumptions on masculinity not only within the context of the show, but also from a Malaysian gendered perspective.